Human Trafficking in Conflict Areas: Social Intelligence Analysis of Indonesian CItizens in Myanmar and Cambodia - Afithasari, Devi; Widodo, Pujo; Kusuma; Setiawibawa, Rachmat; Uksan, Arifuddin (Cita konsultindo, 2025)
The increasing trend of human trafficking crimes involving Indonesian citizens (WNI) in Southeast Asia, particularly in Myanmar and Cambodia, reveals an increasingly complex and organized form of transnational crime. Many TPPO operations now occur in conflict zones such as Myawaddy, Myanmar, which has become a hub for global digital crime networks. This articleexamines TPPO as a form of man-made social disaster as defined by Law Number 24 of 2007concerning Disaster Management. The study focuses on analyzing the role of social intelligence in the stages of early detection, early warning, forecasting, and problem solving to en ly preventand address cross-border human trafficking. This research employs a descriptive qualitativeapproach, drawing on secondary data from government documents, international organizationreports, and media coverage between 2020 and 2025. The findings reveal weaknesses inIndonesia’s social intelligence system, including poor early detection mechanisms, the absence of integrated early warning systems, limited predictive capabilities, and a reactive response pattern. Fragmented data, lack of inter-agency coordination, and limited community involvement exacerbate these gaps. Therefore, a more integrated, preventive, and community-based social intelligence system is urgently needed as part of the national strategy to address TPPO as a crossborder threat and a contemporary social disaster.